Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.4103/0974-1208.44114
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of ART in males with impaired spermatogenesis

Abstract: AIMS:This study was conducted to evaluate the outcomes of assisted reproductive technology (ART) procedures, viz., intrauterine insemination (IUI), in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) in males with impaired spermatogenesis.SETTINGS AND DESIGN:The subjects of the study were infertile couples who were undergoing ART treatment due to male factor indications. The project was designed to correlate the outcome of the ART treatment and its efficacy in different study groups.METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…None of our 11 OA patients with vasectomy had increased sperm chromosomal abnormalities, consistent with earlier results of infertile OA patients and fertile men undergoing vasectomy reversal (18,19). Moreover, good ICSI pregnancy and implantation rates were observed in our OA patients, similar to those described in the literature (3,5), indicating that this level of sperm aneuploidy would not affect reproductive outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…None of our 11 OA patients with vasectomy had increased sperm chromosomal abnormalities, consistent with earlier results of infertile OA patients and fertile men undergoing vasectomy reversal (18,19). Moreover, good ICSI pregnancy and implantation rates were observed in our OA patients, similar to those described in the literature (3,5), indicating that this level of sperm aneuploidy would not affect reproductive outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…However, questions surround the success rates of the ICSI technique in obstructive (OA) and nonobstructive (NOA) azoospermic males. Some authors describe similar and high fertilization and pregnancy rates (3)(4)(5), whereas others report lower ICSI outcomes in NOA than in OA patients (6,7).…”
mentioning
confidence: 93%
“…The selection of patients for ICSI treatment was based on the diagnosis of male factor infertility due to reduced sperm quality (mainly morphological abnormalities). ICSI was the recommended and the most efficient approach in this case to prevent male factor effect [33]. In a collaborative approach, all patients underwent an extensive andrological, gynaecological and cytogenetic examination prior to ICSI to avoid any other bias.…”
Section: Cumulus Cells Collection and Zona Birefringence Analysismentioning
confidence: 99%
“…In these patients, ICSI showed a significantly better pregnancy rate than IUI and IVF. 40,41 Mangoli et al 41 found that ICSI showed a significantly higher pregnancy rate (29%) over IVF (13.2%) for men with OAT, whereas IVF showed a significant advantage over IUI (pregnancy rate of 8%).…”
Section: Discussionmentioning
confidence: 99%